Knowledge, Awareness and Attitude of Medical Students Regarding HPV Infection and HPV Vaccination - Gollu, Aparna Narayana; Gore, Chaitali Ashutosh (Asian Pacific Journal of Cancer Care, 2021)
Background: Cervical cancer is the second commonest cancer among women in India and accounts for 6-29% of cancers among women in India. Human Papilloma Virus (HPV) is a causative agent of the disease. Recent advances in technology have led to introduction of vaccine to prevent HPV infection. The current study aims to assess the awareness among medical students about HPV infection as a causative factor for cervical cancer and their knowledge about HPV vaccination. Assessing the knowledge of vaccination among medical students helps us to understand the level of awareness regarding the same among future doctors. Methods: A questionnaire based study was done on 150 MBBS students from 2nd and 3rd year of Vydehi Medical College, Bangalore,Karnataka, India. Questionnaire consisted of 16 questions of multiple choice type and results were analysed using percentages and chi square test. P value <0.05 was considered significant. Results: Knowledge regarding HPV as a causative agent for cervical cancer was found in 67 (95.7%) of male students and 79 (98.8%) of female students with no statistically significant difference. Awareness about availability of HPV vaccine was seen in 66 (82.5%) females as compared to 50 (71.4%) males with a p value of 0.078, which was not statistically significant. Complete vaccination status was seen in 3 (4.3%) male students and 11 (13.8%) female students with a p value of 0.041 and this association was statistically significant. 1 (1.42%) male student and 1 (1.25%) female student received incomplete vaccination. 25 (35.7%) males and 74 (92.5%) females were willing to get vaccinated with HPV vaccine with p value 0.000, and the association was statistically significant. Conclusion: There was good knowledge among medical students regarding cervical cancer and its prevention. But knowledge regarding HPV vaccine was poor among both males and females. Willingness to get vaccinated in male students was very less compared to female students.